2014
DOI: 10.1111/tpj.12591
|View full text |Cite
|
Sign up to set email alerts
|

The powdery mildew resistance protein RPW8.2 is carried on VAMP721/722 vesicles to the extrahaustorial membrane of haustorial complexes

Abstract: Plants employ multiple cell-autonomous defense mechanisms to impede pathogenesis of microbial intruders. Previously we identified an exocytosis defense mechanism in Arabidopsis against pathogenic powdery mildew fungi. This pre-invasive defense mechanism depends on the formation of ternary protein complexes consisting of the plasma membrane-localized PEN1 syntaxin, the adaptor protein SNAP33 and closely sequence-related vesicle-resident VAMP721 or VAMP722 proteins. The Arabidopsis thaliana resistance to powdery… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
67
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 77 publications
(69 citation statements)
references
References 31 publications
2
67
0
Order By: Relevance
“…8B). In line with this inference, an exocytosis pathway defined by a SNARE complex defined by Vamp721/Vamp722 and SNAP33 has recently been shown to be required for efficient targeting of RPW8.2 vesicles to the EHM (Kim et al, 2014). Third, consistent with the above results, we also found that YFP-HR3's localization to the papilla is BFA sensitive, whereas EHM-targeting of YFP-HR3 (and RPW8.2-RFP) is BFA insensitive (Fig.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…8B). In line with this inference, an exocytosis pathway defined by a SNARE complex defined by Vamp721/Vamp722 and SNAP33 has recently been shown to be required for efficient targeting of RPW8.2 vesicles to the EHM (Kim et al, 2014). Third, consistent with the above results, we also found that YFP-HR3's localization to the papilla is BFA sensitive, whereas EHM-targeting of YFP-HR3 (and RPW8.2-RFP) is BFA insensitive (Fig.…”
Section: Discussionsupporting
confidence: 90%
“…We recently revealed that RPW8.2 [also RPW8.1 when expressed in the haustorium-invaded cells (Ma et al, 2014)] is specifically targeted to the EHM where it enhances formation of the haustorial encasement and promotes onsite H 2 O 2 accumulation and/or triggers hypersensitive response . Specific targeting of RPW8.2 to the EHM requires two basic residue-enriched motifs in RPW8.2 and engages an EHM-oriented specific trafficking pathway (Wang et al, 2013;Kim et al, 2014). Thus, the EHM is the subcellular locale for launching RPW8.2-mediated, haustorium-targeted defenses.…”
mentioning
confidence: 99%
“…Genetic screens for impaired extracellular defense in nonhost resistance to the nonadapted powdery mildew pathogens also identified SYNTAXIN RELATED PROTEIN1 (SYR1), also known as SYP121/PEN1 and PEN2, which encode a plasma membrane-resident syntaxin and a myrosinase, respectively (Leyman et al, 1999;Collins et al, 2003;Lipka et al, 2005;Stein et al, 2006). PEN2 and PEN3 act in the same pathway for extracellular defense, whereas PEN1 functions in a parallel secretory defense pathway (Collins et al, 2003;Kwon et al, 2008;Kim et al, 2014). PEN2 function has been assigned to a glucosinolate metabolic pathway, which comprises biosynthesis of indole glucosinolates (IGs), pathogen-inducible redirection of this biosynthesis through the CYTO-CHROME P450 81F2 (CYP81F2) monooxygenase to 4-methoxyindol-3-ylmethylglucosinolate (4MI3G), and 4MI3G activation by PEN2 myrosinase through deglucosylation (Bednarek et al, 2009).…”
mentioning
confidence: 99%
“…SYP121 forms a complex on the PM in association with two vesicle-associated membrane proteins (VAMPs), VAMP721 and VAMP722 (Collins et al 2003;Kwon et al 2008). VAMP721 and VAMP722 exhibit homology to the rat (Rattus norvegicus) synaptobrevin (SYB) and S. cerevisiae Ykt6p and Sec22p (Baumert et al 1989;Dujon et al 1994;Søgaard et al 1994;McNew et al 1997;Sanderfoot et al 2000;Collins et al 2003;Lipka et al 2007;Kwon et al 2008;Kim et al 2014). Therefore, 4 VAMP protein classes exist (Lipka et al 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, 4 VAMP protein classes exist (Lipka et al 2007). SYP121 also functions with the 33 kilodalton (kD) soluble N-ethylmaleimide-sensitive factor (NSF) adaptor protein (SNAP33), related to the mouse (Mus musculus) SNAP-25 and S. cerevisiae Sec9p (Oyler et al 1989;Collins et al 2003;Kwon et al 2008;Kim et al 2014). PEN1 functions in the formation of a membranous defense apparatus called a cell wall apposition (Aist 1976;Collins et al 2003).…”
Section: Introductionmentioning
confidence: 99%